(untitled) (Cadernos de Sociomuseologia, 2014)
In the countries of southern Europe, the economic adjustment policies being applied are causing a progressive weakening of the museological action in its various forms. Questioned within the transformation process involving a profound change of the management models and of the prevailing values, museums seek a Sustainable Museology. In this context, new museological formulas emerge associating sustainability to social creativity and to valorization of diversity. This is the case of the Costume Museum in São Brás de Alportel (MuT), in the Algarve, and its "Museology on layers". A model based on shared management, taking as its starting point a deep knowledge of the territory, the collective construction of senses and local cultural meanings, and the reframing of ancestral knowledge, with the objective of contributing to an equitable development. In this paper we present the structure, the method and the results of one of the reference projects: Photography, memory and identity (FMId). In this case, a contrastive analysis between the collaborative research and the cartography of meanings associated with pictures of each family is performed. This exercise of memorial archaeology leads to decoding diverse segments of local culture. Its resonances reach every one of the museological functions and processes of MuT, but also each of the families involved in the project, have now a current account of memory in their hometown Museum. Key-words: Museology on layers; photography; cartography; participation.